Using Principal Component Analysis (PCA) to Interpret Geochemical Composition of Toxic Waste - Kouadio, Olivier; Dongo, Kouassi; Ouffoue, Koffi Sebastien; Koffi, Antoine; Kouadio, Maxime Romeo (European Scientific Journal, ESJ, 2025)
The Ivorian Antipollution Center discovered toxic waste from Probo Koala ship in August 21, 2006. This ship had been used by the Trafigura company to refine oil called naphtha of cokéfaction at sea. The refining process involved caustic sodium carbonate washing, which produced toxic waste. This waste was unloaded in 13 areas of the Abidjan district: Akouédo, Abobo, Abobo-Alépé Road (Djibi village), Civile Prison Road (MACA), the industrial zone of Koumassi, and Port-Bouët-Vridi CAP Logistic (Rue Saint-Sylvestre), among others. This situation caused a socio-political crisis and resulted in the deaths of many people. Initial analysis showed that the substances in the toxic waste originated from petroleum processing. To access the environmental impact of this pollution in the Abidjan district (Ivory Coast), samples of the toxic waste were sent for analysis to the Wessling laboratory in France. The results revealed that the waste contained Polycyclics Aromatics Hydrocarbons (PAH), Volatile Aromatics Compound (VAC), Mercaptans, Sulfur molecules, Aliphatic hydrocarbons, Linear hydrocarbons, Total Petroleum Hydrocarbons (TPH), and heavy metals.